Seeing parochially and acting locally: Social exposure, problem identification and social entrepreneurship - Dutta, Sunasir (Journal of Business Venturing, 2019)
Why some communities have greater rates of social entrepreneurship in similar domains is a question of importance to scholars and practitioners alike. Much of the literature in social entrepreneurship begins with a social problem that has been identified, and then analyzes the antecedents of the entrepreneurial process that lead to organizational solutions emerging for those problems. However, why some problems gain traction as being worthy of time and effort in solving, has garnered little attention. We argue that particular problems are more or less salient triggers of action by prospective social entrepreneurs based on the distribution of such problems in the local social environment, rather than aggregate levels of need. Yet, even problems widely experienced as shared, salient, and generally worthy of action might lack the emergence of solutions in fragmented communities, such as those with high levels of residential segregation by race and income. We study this in the context of founding of advocacy and support organizations in the domain of healthcare, and find support for our predictions. We also conducted additional tests to better characterize the findings and test robustness to alternative sources of influence, such as the local pool of potential social entrepreneurs, the role of local ecology, and geographic spillovers from neighboring areas.